Study of effect of fentanyl and tramadol added to low dose bupivacaine in subarachnoid block for caesarean section – a comparative study (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Caesarean section is one of the most common operation. Adjuvent added to low dose bupivacaine for caesarean section is a better option.Objectives The study was designed to observe the effects of fentanyl and tramadol added to low dose bupivacaine in subarachnoid block for caesarean section.Methods Sixty parturient were randomly divided into three groups, 20 (twenty) parturient in each group. Group-A was received 0.5% bupivacaine 7.5 mg (one and half ml) in 0.5ml of 5% dextrose in water-total 2 ml, Group-B was received of 0.5% bupivacaine 5mg with fentanyl 5O μgm -total 2mL. and in Group-C was received 0.5% bupivacaine 5mg with tramadol 50 mg- total 2 ml were used for spinal anaesthesia. Height of sensory block was assessed by pin prick method and quality of motor block was assessed by Bromage scale. Duration of effective analgesia was recorded as the patients request for the first dose of analgesic. APGAR score was recorded at 1 and 5 minute after delivery of the baby.Result The mean duration of block in group-A was 117,75± 22.96; in group-B was 166,00± 29-62 and group-C was 213.00± 27.35 min which was significant among three groups (P = 0.01). The mean change of systolic blood pressure among the three groups at 3 min., 4 min., 5 min., 6 min., 8 min., 9 mim, 10 min., 20 min. and 30 min. after SAB was found significant and the mean change of diastolic blood pressure was significant at 2, 3, 8, 9, 10, 20 min and p value was 0.020, 0.035, 0.058, 0.031, 0.040, 0.063 respectively after SAB. Hypotension occured 7 (seven) patients in group-A; 9 (nine) patients in group-B and 4 (four) patients in group-C. Itching was not found in group-A; 6 patients in group-B and no patient in group-C. Measurement of VAS after SAB was significant among the groups. There were also significant difference of VLAS among the groups in 1st hour (P =0.00049), 2nd hrs (P- 0.007) and 3rd hrs (P = 0.001) after of SAB, and interaction between groups were significant (P =0.001).Conclusion Bupivacaine and tramadol combination may be a better choice for intrathecal anaesthetic agent in comparison to 0.5% of bupivacaine in 0.5ml of 5% dextrose with water or 0.5% of bupivacaine with fentanyl combination.JBSA 2012; 25(2): 41-47